Principles of statutory interpretation - Calnan, Richard (Oxford : Oxford University Press, 2023)
The interpretation of legal texts is, essentially, a question of judgement. But that judgement cannot be exercised arbitrarily. It must be exercised in accordance with the rule of law. Calnan explains this using seven defined principles and provides examples which illustrate how the principles work together.
This edition also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 24, 2023).
Keywords: Law -- Great Britain -- Interpretation and construction; Law; Laws of specific jurisdictions & specific areas of law